Combined effect of compressing fresh concrete and curing regime on bonding performance of high strength repair mortar - Parisa Bahri; Mahmoud Naderi (Heliyon)
High strength concrete (HSC) is highly appropriate for the retrofitting and rehabilitation of reinforced concrete structures due to its low permeability and high bonding strength. However, its low workability and sensitivity to curing conditions pose significant challenges for its implementation in such projects. This study introduces a novel technique to overcome the workability barrier of HSC while enhancing its bonding strength under various curing conditions. To achieve this, four different pressures (0, 0.87, 2.61, and 5.23 MPa) were applied to fresh high strength repair mortar (HSRM) and HSC for durations of 2, 4, and 8 h. Subsequently, different curing methods, including the wet sack method, steam curing method, and the use of curing compounds, were employed. The modulus of elasticity and compressive strength of HSC, in addition to bonding performance between substrate HSC and 28-day compressed HSRM, were evaluated using the “friction-transfer” and “twist-off” techniques, which are standard techniques for measuring the bonding strength of concrete both in the laboratory and in-situ. Also, to further assess the effect of curing regime and pressure on the microstructures of HSRM, SEM images of 28-day HSRM specimens were collected. The results indicated that increasing the pressure to 5.23 MPa and extending the duration to 8 h enhanced the ultimate torsional shear strength between HSRM and substrate HSC by an average of 174%. Additionally, the mechanical properties of HSC were considerably enhanced by applying 5.23 MPa pressure over 8 h. It is worth mentioning that the bonding strength between HSRM and substrate HSC without curing was highly affected by the duration of pressure application compared to the three investigated curing methods. The wet sack curing method was found to be the most effective for enhancing the degree of hydration and increasing the failure torsional shear stress of compressed HSRM specimens.